Creating a duet: The Couples Life Story Approach in the United States and Japan. (July 2016) - Ingersoll-Dayton, Berit; Spencer, Beth; Campbell, Ruth; Kurokowa, Yukiko; Ito, Mio
There is a global need for interventions that help couples who are dealing with dementia. This paper describes the way in which interventionists from the United States and Japan participated in the development of an intervention for dyads in which one person is experiencing memory loss. The 5-week intervention, the Couples Life Story Approach, helps dyads to reminisce about their life together as a couple, to work on their patterns of communication, and to develop a Life Story Book. Based on an analysis of cases conducted in the United States ( n  = 20 couples) and Japan ( n  = 9 couples), this paper highlights the cross-fertilization process that has occurred as interventionists from the two countries have shared their experiences with one another. Using case illustrations, the discussion focuses on the clinical themes that have emerged for couples in the United States and Japan.